Conceptual Design of Interactive Virtual Museum Using Artificial Intelligence and Virtual Reality - Putri, Najwa Azahra (Journal of Computer Science and Research (JoCoSiR), 2024)
Traditional museums face challenges in preserving fragile artifacts and providing immersive experiences due to physical limitations and accessibility issues. This study aims to develop a conceptual design of an interactive virtual museum that integrates virtual reality and artificial intelligence to enhance cultural preservation and public engagement. The research adopts a descriptive qualitative design with a literature-based methodology, focusing on the analysis and synthesis of previous studies related to virtual museums and immersive technologies. The conceptual design emphasizes four main components: a virtual reality module that provides an interactive 3D museum environment, an artificial intelligence module that offers adaptive guidance and recommendations, a database module that stores digital artifacts and interaction records, and a user interface that connects visitors with the system. The results present a comprehensive conceptual framework that illustrates how virtual reality and artificial intelligence can be combined to create a more engaging and accessible museum experience. The study concludes that integrating these technologies offers an innovative solution for digital cultural preservation, enabling people to explore museum collections without physical constraints while maintaining educational and historical values. This conceptual design serves as a foundation for future research and practical implementation of virtual museum systems that promote both cultural sustainability and technological advancement